Anti-collapse performances of steel beam-to-column assemblies with different span ratios. (January 2018) - Meng, Bao; Zhong, Weihui; Hao, Jiping
Abstract: The local failure of one or more structural members of a steel frame could trigger the progressive collapse of the structure. In this study, the anti-collapse performances of different beam-to-column assemblies comprising three columns and two beams were investigated. Three types of specimens with different span ratios (1:0.6, 1:1.0, and 1:1.4) and constructed using welded unreinforced flange-bolted web connections were considered. Static loading tests and numerical simulations were performed, and the local failures of all the specimens were observed to occur in the beam-to-column connection zones under large deformations. Each specimen exhibited multiple peak loads because of the repeated occurrence of local damage. The specimen with equal spans was found to exhibit a higher progressive collapse resistance in the latter phase owing to the synergistic action of the two adjacent beams. It also had a better load transfer mechanism, which enhanced the anti-collapse bearing capacity. Conversely, the peak loads of the specimens with unequal spans decreased with increasing loading displacement owing to the failure of the short beam before the long beam without full realization of catenary action. It was also determined through validated FE models that, when the constraints provided by the side columns were sufficient for the development of flexural and catenary actions in a beam, the assembly constraints provided by the peripheral components amounted to surplus constraints. Furthermore, more comparable linear stiffnesses of the column and beam enhanced their synergistic action and improved the resistance of the steel frame. Highlights: Anti-progressive collapse performance of steel beam-to-column assembly with different span ratios is investigated. Based on double full-span assemblies with welded unreinforced flange-bolted web connections, the performance of anti-collapse is studied. The failure mode, mechanical behavior and load transfer mechanism of three specimens are discussed and analyzed. The effect of boundary constraints of beam end on the anti-collapse performance is investigated.